ANALYSING THE POVERTY REDUCTION EFFECT OF CHINA’S DIRECT INVESTMENT IN BELT AND ROAD COUNTRIES - Song, Min; Regina Garai, Abdullah (Universiti Malaysia Terengganu, 2025)
This study investigates the poverty reduction effect of China’s direct investment in countries along the Belt and Road Initiative (BRI). Using panel data from 63 countries over the period 2009 to 2019, we employ an econometric model and mediation analysis to examine the impact mechanisms. The findings reveal that China’s Foreign Direct Investment (FDI) significantly reduces poverty by stimulating employment and improving infrastructure. Regional disparities are evident, with stronger effects in South and Southeast Asia. The study underscores the significance of targeted investments in infrastructure and job creation, offering actionable insights for policymakers and investors. The empirical results indicate that China’s FDI can significantly reduce the poverty rate of poor families in countries along the Belt and Road, which greatly reduces the number of poor people in these countries and effectively promotes local economic development. In addition, the results contribute to the growing literature on the socioeconomic impacts of international investment and provide a foundation for further exploration into development strategies under the BRI framework.